Hubungan Tingkat Kecemasan dan Tingkat Stres dengan Kejadian Insomnia pada Mahasiswa Fikes yang Menjalani Tugas Akhir di Universitas Abulyatama - Nurul Nazirah; Syukriadi Syukriadi; Nurul Amna (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Nowadays, insomnia symptoms are experienced by many people, especially those who are in the final semester and are working on their final assignments. The common causes of insomnia are anxiety and stress. Therefore, this study tries to investigate the correlation between anxiety and stress levels and the incidence of insomnia among college students completing the thesis at the Health Sciences Faculty of Universitas Abulyatama. This study employs an analytical design with a cross-sectional approach involving 134 college students as the sample chosen using a total sampling technique. The data was analyzed using univariate and bivariate data with the Chi-Square test. The result reveals that from 134 respondents, the majority experienced sleep disorder indicated by 51 students (38, 1%). On the anxiety variable, the majority experienced severe anxiety 36 students (26, 9%), and the variable of stress level indicated that the majority experienced moderate stress 63 students (47%). Based on the Chi-Square test, there is a correlation between the anxiety variable (p=0,008) and stress level variable (p=0,005) towards the incidence of insomnia in final-year students. This study concludes that the incidence of insomnia in final-year students is influenced by anxiety and stress. This study recommends campuses provide information consultation on insomnia, such as health socialization through social media on how to deal with anxiety and stress management.